The Phenomenology of Transparency in Thriller Films - Abuhassan, Lama Bilal; Ali Al Omari, Kifah (Moh’d Khair) (Opción, 1970)
In film theory, transparency is a key concept to know both the truth and the myth of what the spectators watch. This paper attempts to redefine the concept of Transparency by understanding its phenomenology and essence. It also attempts to create a theoretical framework that helps the viewer understand its ultimate meaning. This paper addresses the effect of the phenomenology of transparency on the viewer, both consciously and corporeally by relating it to the concepts of proximity, accessibility and touch. The suggested definition helps to define different forms of transparency, a topic that will be discussed in another paper by the researchers.